A new era for women? Some reflections on blind spots of ICT-based development projects for women's entrepreneurship and empowerment. (4th May 2018) - Güney-Frahm, Irem
Abstract: This article deals with women's empowerment through the use of information and communication technologies (ICT) in development projects. In paying special attention to female visibility in the public sphere and to women's marginalization in the labor market, the article analyzes the shortcomings in ICT-related projects' conceptualization; in particular in those projects that employ ICT to support female entrepreneurship in the name of women's empowerment. It presents theoretical, methodological and ethical arguments for a feminist engagement with contemporary trends in development policy.